2022
DOI: 10.1111/ctr.14585
|View full text |Cite
|
Sign up to set email alerts
|

The type of SARS‐CoV‐2 vaccine influences serological response in kidney transplant recipients

Abstract: Vaccination is a promising strategy to control the ongoing pandemic; however, solid organ recipients tend to develop a weaker immune response to vaccination. Anti-spike SARS-CoV-2 antibodies titers were measured 2-4 weeks post-vaccination completion in 131 KT patients without previous infection. Demographic, clinical, and laboratorial parameters were analyzed to identify which factors contributed to seroconversion. Factors that influenced seroconversion, that occurred in 76 patients (58%), were longer time pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
2
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 15 publications
1
12
2
2
Order By: Relevance
“…Interestingly, time post-transplantation did not affect the response rates in this cohort as has been demonstrated in previous studies with vaccination within 12 months of transplantation negatively impacting immunologic response [ 20 ]. The use of rituximab, tocilizumab, IVIG, and/or ATG also did not influence immune response in this cohort; however, the sample sizes for these factors were small.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Interestingly, time post-transplantation did not affect the response rates in this cohort as has been demonstrated in previous studies with vaccination within 12 months of transplantation negatively impacting immunologic response [ 20 ]. The use of rituximab, tocilizumab, IVIG, and/or ATG also did not influence immune response in this cohort; however, the sample sizes for these factors were small.…”
Section: Discussionsupporting
confidence: 56%
“…There is little data in pediatric KT recipients; however, several small cohort studies of adolescents and young adults have demonstrated similar absence of antibodies post-SARS-COV-2 immunizations [ 18 , 19 ]. Factors associated with poor response rates following a two-dose vaccination schedule include advanced age, immunization within 12 months of transplantation, non-mRNA vaccines, use of mycophenolate mofetil (MMF), or use of more than two immunosuppressant agents [ 17 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Table S3 shows the baseline characteristics of the studies 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , …”
Section: Resultsunclassified
“…Otros autores han encontrado hallazgos similares con tasas de respuesta a dos dosis en trasplantados entre 22 % y 57 % [45,46], siendo más alto al emplear vacunas de ARNm, especialmente ARNm-1273 (47). Correia et al [48] encontraron que los pacientes que recibieron vacunas de ARNm tuvieron tasas significativamente más altas de seroconversión, en comparación con las vacunas de vector de adenovirus (67 % frente a 33 %, P < 0,001). También se ha encontrado que los niveles de protección humoral disminuyen rápidamente también en los trasplantados renales que inicialmente respondieron a la vacunación, independientemente del tipo de inmunoglobulina y del ensayo utilizado.…”
Section: Respuesta Inmunológica (Incluyendo La Respuesta Inmunológica...unclassified